Interpretation on ependymal tumors in the 2021 WHO Classification of Tumors of the Central Nervous System (fifth edition) - PAN Hao; YANG Xue⁃jun; LI Zhi⁃yong; HUANG Guang⁃long; QI Song⁃tao (Chinese Journal of Contemporary Neurology and Neurosurgery, 2021)
In 2021, the WHO released the Classification Tumors of the Central Nervous System (fifth edition). Compared with the revised version of the fourth edition of the WHO Classification of Tumor of the Central Nervous System in 2016, classification of ependymal tumors has many adjustments. Ependymal tumors are classified according to anatomical sites. Several new molecular subtypes are added. Myxopapillary ependymoma is adjusted to WHO grade 2 instead of grade 1. Definition of the ependymoma is deleted. Combined with the relevant literature in recent years, we interpret the updates in this new edition tumors classification about ependymal tumors in order to deepen the understanding of ependymal tumors and standardize the clinical practice.